Patterns of Semen Analysis: Experiences of a Laboratory Catering to Semi Urban Population of Delhi - Jairajpuri, Zeeba S; Rana, Safia; Ali, Manal Ashraf; Pujani, Mukta; Jetley, Sujata (Bangladesh Journal of Medical Science, 2017)
Background:Infertilityis defined as failure of a couple to conceive after one year of regular sexual intercourse. It remains both prevalent and problematic among couples worldwide. The analysis of semen remains the preliminary investigation for males in the workup of infertility in couples.It is a key element in the fertility evaluation of men and permits male reproductive potential to be evaluated in association with possible risk factors. Aim: To assess and analyse the semen characteristics of all the males who presented to our hospital, irrespective of primary or secondary infertility. Material and Methods: This is an observational study conducted in the Department of Pathology, Hamdard Institute of Medical Sciences, Delhi; from Jan 2012 to Oct 2013. Semen of 139 subjects were evaluated and results analyzed. Results: The present study included 139 subjects whose age ranged from 22 years to 48 years with a mean age of 29.42 years. Patients were divided into oligospermia[17%], normospermia[16%] and azoospermia[9%]. 42.5% of the cases had sperm counts in the range of 51-80million/ml. Asthenospermia was seen in 22.1% of the cases.An age specific comparative analysis of the mean sperm counts, total motility and normal morphology revealed a decline in the aaverage values of these parameters with age. Conclusions: Routine semen analysis remains the backbone of the evaluation of the male factor infertility, but it is important to acknowledge the limitation of semen analysis with respect to collection, processing, evaluation, biological variation of the parameters and lack of information on sperm function. A normal semen analysis does not guarantee the fertilization potential of sperm. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.314-319